A reminiscência no Fédon - Casertano, Giovanni (Revista Archai, 2016)
In the Phaedo, the theory of reminiscence seems to have a functional relation with the demonstration of the immortality of the soul, but it is not all: this theory also hides in itself a genuine theory of learning, knowledge and knowing. This appears in two places, in the pages 72e”‘77a and 91e”‘92e. Its functionality seems to be clear in the second mentioned passage: this passage does not add different features from those already given in 72e sqq, but it aims to refute the doctrine of soul/harmony presented by Simmias: if one accepts the theory of anamnesis ”“ and Simmias and Cebes declare themselves to be both persuaded (91e and 92b) ”“ then the theory of soul/harmony cannot be accepted (92c”‘95a). I will be examining the 72”‘77 pages specially. Thus, the aim of this analysis is to show that knowledge is the ordered and meaningful picture of what is known and it is connected to the indispensable idea of “dialogue”, i.e. of mutual refutation, shared construction of knowledge, and common horizon of knowledge. The perspective of this horizon of knowledge, however, goes beyond the limitations of an individual life. In other words, if an individual life is able to overcome its own limitation and to become part of the construction of knowledge and better lives, it will acquire great value and indeed “become immortal”. Keywords: Plato, Phaedo, anamnesis (reminiscence), knowledge.